2003
DOI: 10.1021/je030153c
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Investigation of the Role of Organic Solvents in the Ionization of Azo Dyes Derived from Thienopyridine

Abstract: The effects of different organic solvent + water mixtures on the acidity constants of some azothienopyridine derivatives were studied. The organic solvents used are methanol, ethanol, acetone, and dimethylformamide. The results obtained are discussed in terms of the solvent characteristics. The pK a values of the dyes studied were determined and found to depend largely on both the amount and nature of the organic cosolvent. Hydrogen-bonding interactions of the conjugate base with solvent molecules as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There is, however, confusing reports in the literature concerning the effects of substituents attached to the azo component on the light fastness of the azo dyes shown in structure 1 [8]. On the basis of some studies, it might be concluded that electron-withdrawing substituents increase the photostability of the azo dyes (1) on polyester substrate, concluding that these dyes fade by a reductive process on polyester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, confusing reports in the literature concerning the effects of substituents attached to the azo component on the light fastness of the azo dyes shown in structure 1 [8]. On the basis of some studies, it might be concluded that electron-withdrawing substituents increase the photostability of the azo dyes (1) on polyester substrate, concluding that these dyes fade by a reductive process on polyester.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with a view to understanding the effect of substituents on the photostability of the azo dyes, all‐valence MO calculations employing AM1 and PM3 methods have been carried out on the azo dyes shown in structures 1 , 2 and 3 with different substituents. These dyes were investigated because of the ready availability of their light fastness data [8–10,29]. It is well‐known that the fastness of dye is, to some extent, also dependent on the nature of the substrate.…”
Section: Introductionmentioning
confidence: 99%